Accumulation of salicylic acid in tomato plant under biological stress affects oviposition preference of Bemisia tabaci. Issue 1 (1st January 2019) - Ueda, Hirokazu; Kugimiya, Soichi; Tabata, Jun; Kitamoto, Hiroko; Mitsuhara, Ichiro
ABSTRACT: In field, plants are exposed to multiple biological stresses simultaneously; for example, insect damage and pathogenic virus infection. In this study, we constructed a simple tripartite experimental system using tomato plant, their insect pest Bemisia tabaci (whitefly), and infectious tomato mosaic virus (ToMV). In the choice test, whiteflies laid more eggs on uninfected plant than on ToMV-infected plant. Further, whiteflies hatched more and grew better on the uninfected plant. Salicylic acid (SA) accumulated in infected plants, and the expression of genes involved in SA production and SA-related response was significantly induced. These plant responses against ToMV infection were similar to those against whitefly attack or SA-treated plants. To examine the importance of plant endogenous SA for whitefly preference, we repeated the choice test using the Nah G transgenic tomato that cannot accumulate SA. Whiteflies did not show oviposition preference between Nah G plants with and without ToMV infection or whitefly infestation. Overall, whiteflies prefer healthy plants, and SA accumulation in response to biological stresses is involved in their preference.